The influence of arm strength-flexibility and problem-solving on Petanque athletes' motor skills: implications for sports learning - Nurul Badriyah; Nurul Ihsan; Zulbahri Zulbahri; Ardo Okilanda (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2025)
This study investigates the direct and indirect effects of arm muscle strength, wrist flexibility, and problem-solving ability on shooting accuracy among female Petanque athletes in West Sumatra. Forty athletes were purposively sampled based on active participation in training and competition. Arm muscle strength was measured using a medicine ball throw, wrist flexibility with a goniometer, problem-solving ability via a Likert-scale questionnaire, and shooting accuracy using the standardized FIPJP test. Path analysis revealed that wrist flexibility (β = 0.324, p = 0.046) and problem-solving ability (β = 0.329, p = 0.026) significantly contribute to shooting accuracy, while arm muscle strength showed a positive but non-significant effect (β = 0.269, p = 0.071). Wrist flexibility also significantly influenced problem-solving ability (β = 0.519, p = 0.003), indicating an indirect pathway. These findings suggest that precision-based performance in Petanque relies more on fine motor control and cognitive decision-making than brute strength, and that training programs should emphasize wrist mobility and cognitive drills. Future research should expand participant diversity, include additional physical and psychological factors, and adopt longitudinal or experimental designs to clarify causal relationships.